KEHARUSAN PELAKU USAHA MEMBERIKAN INFORMASI YANG BENAR DITINJAU DARI HUKUM ISLAM DAN UNDANG-UNDANG PERLINDUNGAN KONSUMEN - Azizah, Ninik (Irtifaq, 2015)
The law is needed to regulate social life in all its aspects, including economic activity. There are a synergy of law and economics. Consumer awareness causes most businesses take advantage of the weaknesses of the consumer. Consumers suffered losses doubled, without realizing that they have been cheated. Therefore, this paper attempts to map the legal provisions adopted in Indonesia, namely the Consumer Protection Act (BFL) obligations related businesses in providing product information distribution. The mapping results further compared with the provisions of Islamic Law to note the similarities and differences. Keywords : Business communities, Edar Product Information